Association of DTNBP1 With Schizophrenia: Findings From Two Independent Samples of Han Chinese Population - Yang, Yongfeng; Zhang, Luwen; Guo, Dong; Zhang, Lin; Yu, Hongyan; Liu, Qing; Su, Xi; Shao, Minglong; Song, Men; Zhang, Yan; Ding, Minli; Lu, Yanli; et al. (Frontiers in Psychiatry, 2020)
Objectives: Schizophrenia (SZ) is a complex psychiatric disorder that has a strong genetic basis. Dystrobrevin-binding protein 1 (DTNBP1) is one of the genes thought to be pivotal in regulating the glutamatergic system. Studies have suggested that variations in DTNBP1 confer susceptibility to SZ and clinical symptoms. Here, we performed a two-stage independent verification study to identify polymorphisms of the DTNBP1 gene that might be associated with SZ in the Han Chinese population. Methods: In stage 1, 14 single nucleotide polymorphisms (SNPs) were genotyped in 528 paranoid SZ patients and 528 healthy controls (HCs) using the Illumina GoldenGate assays on a BeadStation 500G Genotyping System. In stage 2, ten SNPs were genotyped in an independent sample of 1031 SZ patients and 621 HCs using the Illumina 660k Genotyping System. Clinical symptoms were assessed using the Positive and Negative Syndrome Scale. Results: There was a significant association related to allele frequency, and a trend association in relation to genotype between SZ patients and HCs at rs4712253 (p = 0.03 and 0.05, respectively). These associations were not evident following Bonferroni correction (p > 0.05 for both). Haplotype association analysis revealed that only two haplotypes (GAG and GAA; rs16876575-rs9464793-rs4712253) were significantly different between SZ patients and HCs (χ2 = 4.24, 6.37, p = 0.04 and 0.01, respectively). In addition, in SZ patients there was a significant association in the rs4964793 genotype for positive symptoms, and in the rs1011313 genotype for excitement/hostility symptoms (p = 0.01 and 0.002, respectively). We found a significant association in the baseline symbol digital modalities test (SDMT), forward-digital span (DS), backward-DS, and semantic fluency between SZ patients and HCs (p< 0.05 for all). Finally, the SNP rs1011313 genotypes were associated with SDMT in SZ patients (p = 0.04). Conclusion: This study provides further evidence that SNP rs4712253 of DTNBP1 has a nominal association with SZ in the Han Chinese population. Such a genotype variation may play a role in psychopathology and cognitive function.